Ensino da vírgula por meio de uma metodologia ativa - Nunes, Júnio Franklin (2020)
Students of all grades, whether in junior school, high school or even higher education, have difficulties in using the comma for several reasons. In my case as a teacher, when analyzing other methodologies and authors during my Master’s program, such as Val (2002), Lobato (2015) and Pilati (2017), I realized that I have a lot of resistance in teaching through methodologies that are not expository. My classes are oftentimes expository once the effective participation of students is minimal: they only receive the information that I write on the board, do not interact and are placed in passivity. Based on these observations, the objective of this research was to develop a proposal for reflective teaching on the use of the comma with my 7th grade students in a school located in the countryside of the State of Minas Gerais. This proposal was in line with the authors cited above, as well as with the guidelines of the National Common Curricular Base and the National Curricular Parameter, which argue for the construction of individuals who consider a range of hypotheses from the world around them. To this end, this proposal was intended for students to reflect on whether or not there were commas in certain statements, that is, to understand the linguistic mechanisms of writing that require the placement or not of a comma, since these mechanisms differ from those of spoken language and demand formal learning, offered by formal instruction. Thus, the proposal was to develop an active teaching strategy in which the center of the teaching was the student and his or her perspective understanding of the content. The intention was to bring a new non-taxonomic, non-prescriptive and non-expository teaching, so that, through reflective teaching, with adequate support in class, students could reach their own conclusions, formalizing the constructed knowledge about the use or not of the comma in written genres.